Museum in the Streets. - Badovinac, Zdenka; Boynik, Sezgin; Kirn, Gal; Piskur, Bojana (Berlin : Revolver Publishing Berlin, 2008)
Alterazioni Video ; Barisic, Velibor ; Barsi, Joze ; Basic, Ajdin ; Testen, Ziga ; Bernik, Viktor ; Cibik, Jasmina ; Fiskin, Vadim ; Habicht, Dejan ; van Heeswijk, Jeanne ; Henriksson, Minna L. ; Huzjan, Istvan Ist ; IRWIN ; Jasa ; Komelj, Miklavz ; Kralj, Gasper ; Kuluncic, Andreja ; Curic, Ibrahim ; Mujic, Said ; Pezic, Osman ; Lazetic, Tanja ; Lovsin, Polonca ; Milikic, Nebojsa ; Pietroiusti, Cesare ; Planiscek, Anja ; Pogacar, Tadej ; Pogacnik, Marko ; Potrc, Marjetica ; Pungercar, Marija Mojca ; Purg, Franc ; radioCona ; Saleci, Renata ; Sedlacek, Saso ; son:DA ; Stancic, Zora ; Stropnik, Mladen ; Span, Nika ; Stromajer, Igor ; Tomazin, Tomaz ; Tot, Endre ; Vogrincic, Matej Andraz ; Cosic, Vuk
Sloveens
Engels
Exhibition. Museum in the Streets. Ljubljana. Moderna Galerija Ljubljana - Museum of Modern Art. 23.09.2008 - 19.10.2008
boek